Answer:
![\large \boxed{x = -1,\, y = -4 \text{ or } (-1, -4)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5j2xrkefu0t0jzj2s3dc5f6ldz2ye28fss.png)
Explanation:
ƒ(x):
-x + y = -3
For easier calculations, add x to each side. Then
y = -3 + x
x = 1: y = -3 + 1 = -2
x = 0: y = -3 + 0 = -3
x = -1: y = -3 + (-1) = -3 - 1 = -4
g(x):
-6x + y = 2
y = 2 + 6x
x = 1: y = 2 + 6(1) = 8
x = 0: y = 2 + 0(1) = 2
x = -1: y = 2 + 6(-1) = 2 - 6 = -4
![\begin{array}{ccc}\mathbf{x}& \mathbf{f(x)}& \mathbf{g(x)}\\\mathbf{1} & -2 & 8\\\mathbf{0} & -3 & 2\\\mathbf{-1} & -4 & -4\\\end{array}\\\text{The table shows that f(x) = g(x) = -4 when x = -1.}\\\text{The solution to both equations is $\large \boxed{\mathbf{x = -1,\, y = -4} \text{ or } \mathbf{(-1, -4)}}$}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/anicszobc0mgn0r8b76zsswhgy9kj2leyv.png)